سياسة دعم الأسعار في الجزائر: الأسس والتحديات - وقادي سالم; صوالح محمد حمزة (جامعة الوادي University of El Oued, 2025)
تستعرض الدراسة دور سياسة الدعم الاجتماعي في الجزائر كأداة لتحقيق السلم الاجتماعي وحماية القدرة الشرائية للفئات الضعيفة، خاصة في مجالات الصحة والتعليم والسكن. ورغم النجاحات الميدانية في تحسين المؤشرات الاجتماعية، إلا أن الدراسة تسلط الضوء على "المفارقة الاقتصادي"؛ حيث تسببت هذه السياسة في ضغط هائل على الخزينة العمومية وأدت إلى عجز في الميزانية. وتخلص النتائج إلى أن استمرار الدعم بصيغته الحالية يواجه تحديات هيكلية، أهمها اتساع الفوارق الطبقية والحاجة الملحة لإعادة بناء الثقة بين السلطة والمواطن لضمان كفاءة وصول الدعم لمستحقيه. This study aims to define the foundations and challenges of the price subsidy policy in Algeria, highlighting its role in maintaining political and social stability across various sectors. While intended to promote social justice and protect the purchasing power of vulnerable groups—improving access to education, healthcare, and housing—the policy faces significant hurdles. These include a lack of trust between policymakers and citizens and a widening gap between the wealthy and the underprivileged. The study concludes that while subsidies have bolstered social welfare, they have negatively impacted the national economy by contributing significantly to the state’s budget deficit.
سياسة العامة
Keywords: دعم الأسعار، القدرة الشرائية، العدالة الاجتماعية، عجز الميزانية، التحويلات الاجتماعية، الاستقرار السياسي، الطبقات الهشة.; Price Subsidies; Purchasing Power; Social Justice; Budget Deficit; Social Transfers; Political Stability; Vulnerable Groups.